2018
DOI: 10.1002/eji.201747458
|View full text |Cite
|
Sign up to set email alerts
|

The immunoproteasome inhibitor ONX‐0914 regulates inflammation and expression of contraction associated proteins in myometrium

Abstract: There are currently no effective treatments to prevent spontaneous preterm labor. The precise upstream biochemical pathways that regulate the transition between uterine quiescence during pregnancy and contractility during labor remain unclear. It is well known however that intrauterine inflammation, including infection, is commonly associated with preterm labor. In this study, we identified the immunoproteasome subunit low-molecular-mass protein (LMP)7 mRNA expression to be significantly upregulated in laborin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…The up‐regulation of the β5i/LMP7 subunit in acini and in macrophages might be linked to Toll‐like receptor pathways, as shown by other groups during infection and ethanol treatment 45,46 . In inflammatory diseases, several reports have associated β5i/LMP7 inhibition or deficiency with diminished cytokine production 47‐49 . Here, we show an opposite effect in which immunoproteasome deficiency correlates with an increased production of pro‐inflammatory cytokines where acini and macrophages are affected.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The up‐regulation of the β5i/LMP7 subunit in acini and in macrophages might be linked to Toll‐like receptor pathways, as shown by other groups during infection and ethanol treatment 45,46 . In inflammatory diseases, several reports have associated β5i/LMP7 inhibition or deficiency with diminished cytokine production 47‐49 . Here, we show an opposite effect in which immunoproteasome deficiency correlates with an increased production of pro‐inflammatory cytokines where acini and macrophages are affected.…”
Section: Discussionsupporting
confidence: 65%
“…45,46 In inflammatory diseases, several reports have associated β5i/LMP7 inhibition or deficiency with diminished cytokine production. [47][48][49] Here, we show an opposite effect in which immunoproteasome deficiency correlates with an increased production of pro-inflammatory cytokines where acini and macrophages are affected. Over the last decade, various studies have found an association between oxidative stress and acinar cell damage, with neutrophils as the central player in this process.…”
Section: Discussionmentioning
confidence: 60%
“…ONX-0914 displayed a higher inhibitory activity towards immunoproteasome β5i (IC50 5.7 nM) as compared to the constitutive proteasome β5c subunit (IC50 54 nM) [258]. ONX-0914 has been proven to be effective in the treatment of inflammatory disorders by specifically targeting immunoproteasome [164,259]. This indicates a therapeutic potential for anticancer therapies where the activity of immunoproteasome is upregulated.…”
Section: Onx-0914mentioning
confidence: 95%
“…Our findings are in good congruence with data obtained previously using broad specificity proteasome inhibitors on A549 cells [ 31 ], human hepatocytes [ 32 ], prostate cancer cells [ 33 ], triple negative breast cancer cells [ 52 ], ovarian cancer cells [ 53 ], and lung epithelial and monocytic cells including THP-1 [ 54 ]. At the same time, decreased CXCL8 expression following ONX-0914 treatment was reported in human myometrial cells and tissues [ 55 ]. Though such discrepancy might be associated with differences in cellular origin and microenvironment.…”
Section: Discussionmentioning
confidence: 94%